Distinct systemic immune networks define severe vs. mild COVID-19 in hematologic and solid cancer patients - Pignataro-Oshiro, Flávio; Figueiredo, Amanda B.; Galdino, Nayane A. L.; Morais, Katia L. P.; Dutra, Walderez O.; Silva, Bianca Grassi de Miranda; Feriani, Diego; Abrantes, Flávia de Azevedo; Silva, Ivan Leonardo Avelino França e; Filho, Jayr Schmidt; Framil, Juliana Valéria de Souza; Cesca, Marcelle Goldner; et al. (Frontiers in Immunology, 2023)
The COVID-19 pandemic, caused by the coronavirus SARS-CoV-2, has impacted health across all sectors of society. A cytokine-release syndrome, combined with an inefficient response of innate immune cells to directly combat the virus, characterizes the severe form of COVID-19. While immune factors involved in the development of severe COVID-19 in the general population are becoming clearer, identification of the immune mechanisms behind severe disease in oncologic patients remains uncertain. Here we evaluated the systemic immune response through the analysis of soluble blood immune factors and anti-SARS-CoV-2 antibodies within the early days of a positive SARS-CoV-2 diagnostic in oncologic patients. Individuals with hematologic malignancies that went on to die from COVID-19 displayed at diagnosis severe leukopenia, lower antibody production against SARS-CoV-2 proteins, and elevated production of innate immune cell recruitment and activation factors. These patients also displayed correlation networks in which IL-2, IL-13, TNF, IFN-gamma, and FGF2 were the focal points. Hematologic cancer patients that showed highly networked and coordinated anti-SARS-CoV-2 antibody production, with central importance of IL-4, IL-5, IL-12A, IL-15, and IL-17A, presented only mild COVID-19. Conversely, solid tumor patients that had elevated levels of inflammatory cytokines IL-6, CXCL8, and lost the coordinate production of anti-virus antibodies developed severe COVID-19 and died. Patients that displayed positive correlation networks between anti-virus antibodies, and a regulatory axis involving IL-10 and inflammatory cytokines recovered from the disease. We also provided evidence that CXCL8 is a strong predictor of death for oncologic patients and could be an indicator of poor prognosis within days of the positive diagnostic of SARS-CoV-2 infection.